The acceptance of social networking technologies at National Sport Council (NSC) / Nik Rahimah Nik Mansoor - Nik Mansoor, Nik Rahimah (2015)
This study aims is to examine the attitude of workers at National Sports Council on how they use social networking technologies at their workplace. Social networking technologies is defined as the communication methods that is used the World Wide Web as a platform for creating the community. The sample of this study is 60 respondents consists of 5 departments at National Sports Council, which are Human Resources and Administration, Sports Facilities, Coaching, Athletes and Paralympic. However, there are only 50 respondents who answered to the questionnaires given. Based on the findings, I found that there a significant between attitude of workers towards social networking technologies between the factors of Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment.